(untitled) - Janet Schaeffer ...[et al.] (Princeton, New Jersey, 1996)
This book measures verbal (sentence correction, reading comprehension, critical reading), quantative (data sufficiency, problem solving), and analytical writing skills (analysis of an issue, analysis of an argument). It is used by graduate schools of business to access the qualifications of applicants to graduate management programs.
Keywords: graduate management admission test,management - examinations, questions, etc..